IOP Conference Series: Earth and Environmental Science - Kuznetsova; Begunova; Romanenko specialist in the field of ecology and life safety head of the Department of Tomsk Polytechnic University, doctor of chemical Sciences; Solodsky specialist in the field of ecology and life safety Associate Professor of Yurga technological Institute of Tomsk Polytechnic University, candidate of technical sciences (2018)
Analysis of the current hygienic situation in the welding production showed that the intensification of welding processes involves the deterioration of air quality, which negatively affects the welders health. Respiratory effects seen in full-time welders have included bronchitis, airway irritation, lung function changes, and a possible increase in the incidence of lung cancer. The metal concentration in the air of the working area have been determined using the photometric method of analysis, which involves the stage of decomposition of the sample material before analysis. However, losses of the analyzed elements are possible when the sample is decomposed. The X-ray fluorescence method of analysis has the advantage of being nondestructive. The investigations shown the data of photometric determination of metals in welding aerosols is 1.5(-:)2 times lower than the results of X-ray fluorescence analysis.